NANOSTRUCTURIZATION IN FOUNDRY PROCESSES - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия)
It is shown that at crystallization of alloys the sophisticated nanostructural processes have place. The nanocrystals of phases, their atoms, the centers of crystallization of dendrites, surface-active elements, gases, modifying elements, poorly soluble impurity elements generally participate in these processes. Their activity and intensity of abstraction of heat during crystallization define the structure of castings.